2022
DOI: 10.12911/22998993/143998
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Surface Water Quality of Four Rivers in Jayapura Regency, Indonesia: CCME-WQI Approach

Abstract: In Indonesia, the river water quality has been determined based on Government Regulation of the Republic of Indonesia No. 22 of 2021. This study aimed to determine the quality of surface water from the Damsari, Jabawi, Kleblow, and Komba Rivers in Jayapura Regency based on the monitoring data from 2016 to 2019. The CCME-WQI method is used to determine the status of rivers based on river water quality standards (class 1 to class 4). The results of the study showed that the parameters of water temperature, TDS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This indicated the effect of discharging of treated wastewater in the Nile River. Many previous studies indicated the effect of wastewater on environmental characteristics of surface water (Abdel-Satar et al 2017 ; Berger et al 2017 ; Onwona Kwakye et al 2021 ; Rahman et al 2021 ; Abdo et al 2022 ; Tanjung et al 2022 ). The microbial respiration as well as decomposing activities in wastewater consume part of the dissolved oxygen, affecting the pH value reflected in the changes of the other parameters like increasing of values of nutrients and NH 4 (Onwona Kwakye et al 2021 ; Abdo et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated the effect of discharging of treated wastewater in the Nile River. Many previous studies indicated the effect of wastewater on environmental characteristics of surface water (Abdel-Satar et al 2017 ; Berger et al 2017 ; Onwona Kwakye et al 2021 ; Rahman et al 2021 ; Abdo et al 2022 ; Tanjung et al 2022 ). The microbial respiration as well as decomposing activities in wastewater consume part of the dissolved oxygen, affecting the pH value reflected in the changes of the other parameters like increasing of values of nutrients and NH 4 (Onwona Kwakye et al 2021 ; Abdo et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Total suspended solids (TSS) consist of silt, organic and inorganic materials, fine sand, and micro-organisms, which originate from soil erosion and are carried to water bodies. Suspended material has a negative impact on water quality because it reduces the penetration of sun light into water bodies, increasing water turbidity and hindering the growth of producer organisms (Syafaat et al 2021;Wasielesky et al 2017;Tanjung et al 2022). The impact of high suspended solids in waters causes reduced levels of dissolved oxygen in the water, directly affecting biota's survival in the waters (Liu et al 2016) Based on observation results, the water temperature ranged from 23 to 29 o C, which is within the water quality standards for biota.…”
Section: Water Quality Parametersmentioning
confidence: 99%
“…Many rivers have undergone water quality degradation and pollution (Tanjung et al, 2022). The problem of water pollution makes it very difficult to keep the rivers' water quality within the acceptable limits allowed for drinking, industrial and agricultural uses, so determining water quality requires certain conditions for water's physicochemical or biological properties (Radaideh, 2022).…”
Section: Introductionmentioning
confidence: 99%